Feasibility and safety of combined cytokine adsorption and continuous veno-venous hemodialysis with regional citrate anticoagulation in patients with septic shock. Issue 1 (January 2020) - Dimski, Thomas; Brandenburger, Timo; Slowinski, Torsten; Kindgen-Milles, Detlef
Introduction: Septic shock is characterized by severe metabolic and hemodynamic alterations. It is often accompanied by acute kidney injury. A new adjunct treatment is hemoadsorption using a cytokine adsorber in line with continuous veno-venous renal replacement therapy. We studied the feasibility, efficacy, and safety of cytokine adsorption with citrate-anticoagulated continuous veno-venous hemodialysis (regional citrate anticoagulation–continuous veno-venous hemodialysis). Methods: In 11 patients with septic shock and acute kidney injury stage 3, we studied 12 cycles of cytokine adsorption and regional citrate anticoagulation–continuous veno-venous hemodialysis. We monitored parameters of citrate anticoagulation, circuit lifetime, laboratory parameters, hemodynamics, and vasopressor demand. Results: Ten out of 12 adsorber/continuous veno-venous hemodialysis circuits reached the target lifetime of 24 h for the adsorber. One system clotted and one was stopped for non-device-related reasons. Nine of the remaining continuous renal replacement therapy circuits reached 72 h lifetime. With default settings for regional citrate anticoagulation, serum ionized calcium and pH were in the normal range. Urea and creatinine were reduced significantly, and norepinephrine dose decreased from 0.47 (±0.09) to 0.16 (±0.04) µg/kg/min ( p = 0.016) after 24 h. Discussion: We show that combined cytokine adsorption/continuous veno-venous hemodialysis is effective to control pH, to reduce urea and creatinine, and to improve hemodynamics by reducing norepinephrine doses in patients with septic shock. It can be applied safely with standard settings of regional citrate anticoagulation rendering sufficiently long filter lifetimes for the adsorber and the continuous veno-venous hemodialysis circuit. Further studies are on the way to investigate whether these effects translate into improved outcomes in septic shock patients.